The Pied Piper: Prizes, Incentives, and Motivation Crowding-in - Luigino Bruni; Vittorio Pelligra; Tommaso Reggiani; Matteo Rizzolli (Masaryk University, Faculty of Economics and Administration, 2019)
In mainstream business and economics, prizes such as the Presidential Medal of Freedom are understood as special types of incentives, with the peculiar features of being awarded in public, and of having largely symbolic value. Informed by both historical considerations and philosophical instances, our study defines fundamental theoretical differences between incentives and prizes. The conceptual factors highlighted by our analytical framework are then tested through a laboratory experiment. The experimental exercise aims to analyze how prizes and incentives impact actual individuals' behavior differently. Our results show that both incentives (monetary and contingent) and prizes (non-monetary and discretional rewards) boost motivation to perform if awarded publicly, but only prizes crowd-in motivation promoting virtuous attitude.
Keywords: B1; D03; J33; 330; incentives; prizes; awards; crowding-in; meaning; intrinsic motivation